Pelatihan Manajemen Pendidikan dan Metode Mengajar Islami Bagi Guru TK dan TPQ Yayasan Asy-Syifa - Maman Abdurrahman; Nunung Nursyamsiyah; Asep Sopian; Eneng Komariyah Maimun RNM (Jurnal Manajemen Pendidikan Dasar, Menengah dan Tinggi [JMP-DMT], 2023)
This study aims to provide training as a means of strengthening knowledge and skills regarding education management and Islamic teaching methods for kindergarten and TPQ teachers at the Asy-Syifa Banjar foundation. The method used is descriptive with a qualitative approach. Data collection techniques through; training, packages and field notes. Data analysis techniques by reducing, presenting data and drawing conclusions from existing data. Based on the data it was found that most of the Asy-Syifa foundation's teachers already had knowledge of educational management and Islamic teaching methods. However, with the provision of training, the acquisition of insight and mastery of the skills and abilities of teachers increase evenly and have a good influence of around 70-80%. This training also has a positive impact on student learning outcomes because teachers apply educational management and use methods well. Apart from that, there are several aspects of training that are well affected by this, namely curriculum, infrastructure, student affairs, assessment and finance.